Percutaneous lordoplasty for the treatment of severe osteoporotic vertebral compression fractures with kyphosis - Song, Tengfei; Sun, Fan; Liu, Shu; Ye, Tianwen (Frontiers in Neurology, 2023)
Objective The study aimed to explore the safety and effectiveness of percutaneous lordoplasty (PLP) in the treatment of severe osteoporotic vertebral compression fracture (OVCF). Methods Included in this prospective study were patients with single-segment acute severe OVCF who were treated with PLP in our institution from July 2016 to October 2019. Patients' back pain and quality of life were assessed using the visual analog scale (VAS) and SF-36 scores. Lateral X-ray radiography of the spine was performed to measure the vertebral height, vertebral kyphotic angle, and segmental kyphotic angle, and to evaluate the outcome of fracture reduction and kyphotic correction. Intra-and postoperative complications were recorded. Results Of the 51 included patients, 47 patients were followed up for 12 months. The VAS score decreased from preoperative 7.33 ± 1.92 to postoperative 1.76 ± 0.85 at the 12th month (p < 0.05), and the SF-36 score increased from preoperative 79.50 ± 9.22 to postoperative 136.94 ± 6.39 at the 12th month (p < 0.05). During the 1-year follow-up period, the anterior height of the vertebral body increased significantly from preoperative 10.49 ± 1.93 mm to 19.33 ± 1.86 mm (p < 0.05); the posterior height of the vertebral body increased insignificantly from preoperative 22.23 ± 2.36 mm to 23.05 ± 1.86 mm (p > 0.05); the vertebral kyphotic angle decreased significantly from preoperative 18.33° ± 11.49° to 8.73° ± 1.21° (p < 0.05); and the segmental kyphotic angle decreased significantly from preoperative 24.48° ± 4.64° to 11.70° ± 1.34° (p < 0.05). During the 1-year follow-up period, there was no significant difference in the radiologic parameters, VAS scores, and SF-36 scores, between the 1st day and the 12th month of post-operation (P > 0.05). No nerve damage occurred in any of the cases. Intraoperative cement leakage occurred in six cases, and the fracture of the adjacent vertebral body occurred in one case. Conclusion PLP can well reduce the risk of fracture and achieve good kyphotic correction and may prove to be a safe, cost-effective and minimally invasive alternative option for the treatment of severe OVCF with kyphotic deformity.